O odpowiedzialności za słowo pisane przy wydawaniu drukiem XX-wiecznych źródeł do dziejów Polaków na ziemiach białoruskich. Casus edycji części II „Wspomnień 1847-1928” Edwarda Woyniłłowicza - Jurkowski, Roman (Przegląd Wschodnioeuropejski, 2025)
The article concerns historical methodology. It addresses the important issue of maintaining scientific correctness in editions of historical sources concerning the second half of the 19th century and the beginning of the 20th century. Using the example of a handwritten diary from 1921-1928 written by Edward Woyniłłowicz, a prominent Polish landowner from Belarusian lands, published in 2016, he discusses the errors and omissions made by the publishers. He draws attention to the inaccurate and incorrect reading of many words from the manuscript, especially surnames, first names and geographical names. He criticizes the lack of scientific apparatus in the form of footnotes and an index of geographical names. It lists numerous factual errors made in the personal index. At the same time, it provides guidance to other editors on how to follow scientific procedures when publishing historical sources from the 19th and early 20th centuries.